Design of Generator Stator Protection 100% Using Overvoltage and Undervoltage Schemes - Mashar, Ali; Firdausi, Maula Zahara; Mudawari, Achmad; Mulyadi, Achmad Deni; Sodiq, Djafar (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
Nowadays, there are still many high capacity generators have not yet protected completely from their internal ground faults. They still rely on differential and over current relays. It is seen that this relay will reduce their sensitivities when applied to generators with high impedance grounding systems. To overcome such problem, a combination protection scheme of the neutral overvoltage (59N) and neutral undervoltage third harmonics (27N3) is developed. This paper aims to design the protection scheme for high capacity generators. This paper demonstrates the designing of neutral grounding transformer (NGT) system, the relay settings and reviewing of their sensitivities. To clarify the concepts this study uses a generator 802 MVA, 22.8 kV as object. The results show that the protection scheme is very effective to protect 100% of generator stator with relays overlapping of 31.5%. It needs NGT transformer with capacity of only 28.33 kVA, 15000/240 V, and the secondary resistor of 0.38,117 kW. This paper can hopefully be used as one reference for protection system engineers to design or develop protection schemes in their fields especially whose generator has not equipped yet with such protection scheme.